Genetic Control of Osmoadaptive Glycine Betaine Synthesis in Bacillus subtilis through the Choline-Sensing and Glycine Betaine-Responsive GbsR Repressor - Nau-Wagner, Gabriele (American Society for Microbiology, 2012)
Synthesis of the compatible solute glycine betaine confers a considerable degree of osmotic stress tolerance to Bacillus subtilis. This osmoprotectant is produced through the uptake of the precursor choline via the osmotically inducible OpuB and OpuC ABC transporters and a subsequent two-step oxidation process by the GbsB and GbsA enzymes. We characterized a regulatory protein, GbsR, controlling the transcription of both the structural genes for the glycine betaine biosynthetic enzymes (gbsAB) and those for the choline-specific OpuB transporter (opuB) but not of that for the promiscuous OpuC transporter. GbsR acts genetically as a repressor and functions as an intracellular choline sensor. Spectroscopic analysis of the purified GbsR protein showed that it binds the inducer choline with an apparent K(D) (equilibrium dissociation constant) of approximately 165 μM. Based on the X-ray structure of a protein (Mj223) from Methanococcus jannaschii, a homology model for GbsR was derived. Inspection of this GbsR in silico model revealed a possible ligand-binding pocket for choline resembling those of known choline-binding sites present in solute receptors of microbial ABC transporters, e.g., that of the OpuBC ligand-binding protein of the OpuB ABC transporter. GbsR was not only needed to control gbsAB and opuB expression in response to choline availability but also required to genetically tune down glycine betaine production once cellular adjustment to high osmolarity has been achieved. The GbsR regulatory protein from B. subtilis thus records and integrates cellular and environmental signals for both the onset and the repression of the synthesis of the osmoprotectant glycine betaine.